(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Coronary artery disease (CAD) is a leading cause of morbidity and mortality worldwide, accounting for 7.4 million of 17.9 million annual cardiovascular deaths. Acute coronary syndrome (ACS) is a symptomatic subset of CAD often associated with myocardial infarction, and includes ST-elevation (STEMI) and non-ST-elevation myocardial infarction (NSTEMI). Atherosclerosis is a systemic process; hence peripheral arterial disease (PAD) frequently coexists with CAD as a manifestation of diffuse atherosclerosis. Many CAD patients have coexistent PAD that is asymptomatic and underdiagnosed . Early identification of PAD in ACS patients is important for secondary prevention and risk stratification, but the local frequency of PAD in ACS is not well established. Objective: To determine the frequency of PAD in patients with CAD presenting with ACS to a tertiary care hospital, using ankle-brachial index (ABI) screening, and to analyze associations with patient demographics. Methodology: A cross-sectional study was conducted at the Cardiology Department of a Lady Reading Hospital Peshawar Pakistan. Over a 6-month period from May–Nov 2024, 159 patients aged 40–70 years with ACS (STEMI or NSTEMI confirmed by clinical, ECG and biomarker criteria) were enrolled by consecutive sampling. Patients with previously known PAD, limb deformity, edema, or incompressible arteries (ABI >1.3) were excluded. Demographic data (age, gender, body mass index [BMI], and CAD duration) were recorded. PAD was assessed by measuring ABI using an automated device after 15 minutes of supine rest; PAD was defined as ABI <0.90 in either leg (without prior PAD history). Frequency of PAD was calculated. Patients were stratified by age, gender, BMI, and CAD duration to evaluate effect modifiers; comparisons used chi-square tests with p ≤ 0.05 as significant. Results: Of the 159 ACS patients (mean age 56.8 ± 9.5 years, 78% male), PAD (ABI <0.9) was detected in 11 patients, yielding a PAD frequency of 6.9% (95% confidence interval 3.0–10.8%). Among those with PAD, 4 (36%) reported intermittent claudication symptoms, while 7 (64%) were asymptomatic (incidentally identified via ABI). Patients with PAD were older on average than those without PAD (mean age 62 vs 55 years, p = 0.03). In patients aged ≥60 years, PAD prevalence was 20.5%, significantly higher than in those <60 years (2.7%, p < 0.001). PAD frequency was slightly higher in males (7.2%) than females (5.9%), but this difference was not statistically significant (p = 0.75). No significant associations were found between PAD presence and BMI or duration of known CAD (p > 0.05 for both). Conclusion: In this cohort of ACS patients, about 7% had coexisting PAD as determined by ABI screening. This relatively sizable minority underscores the importance of routine PAD screening in ACS patients. Early detection of PAD allows for more comprehensive cardiovascular risk management. Our findings, in line with regional data showing 7–8% PAD prevalence in CAD, highlight that even asymptomatic PAD is prevalent in ACS and merits attention to improve secondary prevention and outcomes.